2009
DOI: 10.1159/000208805
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rate Control on Speech Rate and Intelligibility of Dysarthric Speech

Abstract: Purpose: This study investigated the effect of rate control methods (RCMs) on speaking rate (SR), articulation rate (AR), and intelligibility in dysarthric speakers. Method: Nineteen dysarthric patients (7 unilateral upper motor neuron dysarthria, 6 hypokinetic, 3 flaccid, 3 ataxic) participated. SR, AR and intelligibility ratings were determined on the basis of 1-min recorded reading passages. Seven RCMs were applied: voluntary rate control, hand tapping, alphabet board, pacing board and delayed auditory feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
6
25
0
Order By: Relevance
“…These results are in accordance with those of other studies [11][12][13][14][15][16][17][18][19][20] and our previous study [5] , and confirm that most RCMs applied in clinical practice to reduce speech rate are effective. The RCMs that most effectively reduced AR and SR were pacing board, hand tapping and alphabet board.…”
Section: Effect Of Rate Control On Ar and Srsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in accordance with those of other studies [11][12][13][14][15][16][17][18][19][20] and our previous study [5] , and confirm that most RCMs applied in clinical practice to reduce speech rate are effective. The RCMs that most effectively reduced AR and SR were pacing board, hand tapping and alphabet board.…”
Section: Effect Of Rate Control On Ar and Srsupporting
confidence: 93%
“…The majority of the participants with significantly improved intelligibility had SRs and ARs within normal boundaries or even decreased rates. These results add credence to the results of the initial study [5] and the findings of Jaeger et al [24] who found that individuals with dysarthria tend to speak near the upper limit of their SR.…”
Section: Characteristics Of Patients Who May Benefit From Rate Controlsupporting
confidence: 86%
See 3 more Smart Citations